Odpowiedzi

2009-11-30T18:34:13+01:00
A)(x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
b)(2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
c)(4a-1)(2-3a)=8a-12a²-2+3a=11a-12a²-2
d)(x+pierwiastek5 )(x-pierwiastek5) =x²-x/5/+x/5/-/25/=x²-5
między ukośnikami są pierwiastki
9 2 9
2009-11-30T18:34:57+01:00
A.) 2x kwadrat-x+14x-7= 2x kwadrat+13x-7
B.) 2a kwadrat+8a-a-4=2a kwadrat+7a-4
c.)8a-12a kwadrat-2+3a=-12a kwadrat+11a-2
d.) x kwadrat -x pierwiastek z 5 + x pierwiastek z 5 - 5 = x kwadrat - 5
9 2 9
Najlepsza Odpowiedź!
2009-11-30T18:34:22+01:00
A) = 2x^2 - x +14x - 7 = 2x^2 + 13x - 7
b) = 2a^2 + 8a - a - 4 = 2a^2 + 7a - 4
c) = 8a - 12a^2 - 2 + 3a = -12a^2 + 11a - 2
d) = x^2 - 5
10 2 10